Strategi Pengelolaan Stres Kerja Dalam Upaya Peningkatan Kinerja Karyawan Pada PT. Prospera Consulting Engineers - Tri Nur Azizah; Bambang Sutarto (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the factors that cause work stress and its impact on employee performance, as well as formulate strategies for managing work stress using a SWOT analysis at PT Prospera Consulting Engineers. This research employs a qualitative method with a case study approach through in-depth interviews with one key informant and five supporting informants from various divisions with extensive tenures. The findings indicate that work stress mainly arises from fluctuating workloads with high intensity during specific periods, role conflicts and multitasking demands, the lack of clear Standard Operating Procedures (SOP), and the continued use of manual administrative systems. External factors such as tight project deadlines and industry competition also contribute to increased stress levels. Despite these challenges, strong interpersonal relationships, a family-oriented work culture, and a high level of employee responsibility help maintain optimal performance. Employee performance remains achievable even under stressful conditions, indicating the presence of challenge stressors that motivate employees to work harder, although they may affect psychological well-being in the long term. The SWOT analysis produces several strategic recommendations, including strengthening SOPs, implementing digital systems, adding human resources, enhancing employee training and skill development, and providing recognition and improved welfare programs. This study concludes that effective work stress management is essential for sustaining employee performance and supporting the long-term operational stability of the company